Accountants‟ perceptions regarding to business and profession ethics (A study on the alumnus of STIE Perbanas Surabaya) - Dewi Setyorini; Nurul Hasanah Uswati Dewi (Universitas Hayam Wuruk Perbanas, 2015)
This study is aimed to determine the differences in the perception of the accounting student alumnus of STIE Perbanas Surabaya regarding the ethics of business and profession based on gender. The type of data used is primary data using question-naires. The sampling technique is using non-probability samples based on purposive sampling technique. The number of samples processed is 85 respondents from the accounting student alumnus of STIE Perbanas Surabaya. The statistical analysis tool is the Mann Whitney Test using SPSS version 16.0. The first hypothesis of this study can be concluded that there are differences in the perceptions of the account-ing student alumnus regarding the ethics of business and accountant profession based on gender. The second hypothesis indicates that there is no difference in the perception of the accounting student alumnus regarding the ethics of business and accountant profession based on gender, which has a significance level under 0.05 or 5 percent.